First-row early transition metal complexes with a highly sterically demanding triisopropylphenyl amino triphenolate ligand: synthesis and applications. Issue 26 (8th March 2019) - Bae, Dae Young; Park, Gyeong Su; Ko, Nakeun; Son, Kyung-sun; Lee, Eunsung
Abstract : A highly sterically demanding amino triphenolate ligand was successfully synthesized, and early transition metal complexes (Ti, V, Cr, and Mn) supported by the ligand were also obtained and fully characterized. Abstract : Amino triphenolate ligands have been widely used for the synthesis of various transition metal complexes aiming at various applications such as ring-opening polymerization, olefin polymerization, and sulfoxidation. However, the introduction of highly sterically demanding aromatic substituents, such as triisopropylphenyl (TRIP), to the amino triphenolate ligand has not been previously reported probably due to the synthetic difficulty. In six-step reactions using commercial materials, a highly sterically demanding amino triphenolate ligand was successfully synthesized, and early transition metal complexes (Ti, V, Cr, Mn) supported by the ligand were also obtained and fully characterized. In addition, titanium and chromium complexes were further used for catalytic sulfoxidation, and polymerization of ethylene, respectively.